Determinants of attenuation in the envelope protein of the flavivirus Alfuy - Prow, N.; May, F.; Westlake, D.; Hurrelbrink, R.; Biron, R.; Leung, J.; McMinn, P.; Clark, D.; Mackenzie, John; Lobigs, M; Khromykh, A.; Hall, R. (Society for General Microbiology, 2011)
Murray Valley encephalitis virus (MVEV) is a mosquito-borne flavivirus endemic to Australia and Papua New Guinea. Most strains of MVEV cause potentially fatal cases of encephalitis in humans and horses, and have been shown to be highly neuroinvasive in weanling mice. In contrast, the naturally occurring subtype Alfuy virus (ALFV) has never been associated with human disease, nor is it neuroinvasive in weanling mice, even at high doses. To identify viral factors associated with ALFV attenuation, a chimeric infectious clone was constructed containing the structural genes premembrane (prM) and envelope (E) of ALFV swapped into the MVEV genome. The resulting virus (vMVEV/ALFVstr) was no longer neuroinvasive in mice, suggesting that motifs within prM–E of ALFV confer attenuation. To define these motifs further, mutants were constructed by targeting divergent sequences between the MVEV and ALFV E proteins that are known markers of virulence in other encephalitic flaviviruses. MVEV mutants containing a unique ALFV sequence in the flexible hinge region (residues 273–277) or lacking the conserved glycosylation site at position 154 were significantly less neuroinvasive in mice than wild-type MVEV, as determined by delayed time to death or increased LD50. Conversely, when the corresponding MVEV sequences were inserted into the vMVEV/ALFVstr chimera, the mutant containing the MVEV hinge sequence was more neuroinvasive than the parental chimera, though not to the same level as wild-type MVEV. These results identify the hinge region and E protein glycosylation as motifs that contribute to the attenuation of ALFV.